Strategi Pemasaran dan Inovasi Produk untuk Meningkatkan Volume Penjualan “Ketan si Emak” - Maknunah, Nur Saidatul; Rahmi, Vembri Aulia (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This is a new author's manual and a template for Resligion Education Social Laa Roiba Journal (RESLAJ). Published every February and August since 2019. Articles must start with Article Title followed by Author Name and Affiliate Address and abstract. This part of the UMKM Ketan Si Emak is one of the traditional foods in the village of Gumeno Village. The reason why the author is interested in conducting research is because researchers are interested in the marketing strategies and product innovations that are appliedin Ketan Si Emak MSMEs. MSMEs have a central role in the Indonesian economy. Apart from having a central role in the absorption of labor and the Indonesian economy, MSMEs can also play a role as a controller for distributing labor. Indonesia's economy, MSMEs can also act as a controller to distribute the results of development to all corners and regions. the results of development to all corners and regions in Indonesia. The purpose of this study was to determine the marketing strategy and product innovation in Ketan Si Emak MSMEs. Si Emak. Innovation is ideas for change and development to meet customer needs. Marketing is relationship between sellers and buyers to conduct transactions for goods or services. or service. This type of research uses descriptive research with using qualitative research methods. The location of Ketan Si Emak at Mrs. Munaikah's house located on Jalan Beji, RT 11 RW 05 Gumeno Village, Gresik Regency, East Java. East Java.